LEVERAGING USERS TO BREAK CYBER KILL CHAIN - Kokofi, Charles (My University, 2019)
Cyber kill chain defined the chronological strategies that attackers follow in invading information system with the hope of reducing the exponential increase in attacks by equipping organizations and technological stakeholders to revise and build a resilient defensive strategy capable of identifying and preventing attack. Considering how well resourced these attackers, using complicated tools and techniques such as customised attacker vectors and weapons capable of subverting any system or network calls for a counter-productive strategy such as attack surface reduction. Breaking the cyber kill chain using attack surface reduction involve limiting the success of an attacker at every stage of the cyber kill chain. Attack surface reduction involves controlling user behaviours, use of efficient and robust technologies and implementation of a resilient attack defence model. Leveraging the cyber kill chain would be released through evaluation and analysis of technologies, defense models to determine the efficiency and robustness, review of related literatures and implementation strategies capable of subverting the success of an attacker.
Keywords: Hacking, cyber kill chain, attack vectors, defense model, perimeter defense, defense in depth, defense in breadth, attack surface reduction